Optical and Mott-Schottky Studies of Ternary MoSSe Thin Films Synthesized by Electrochemical Route - T., Joseph Sahaya Anand; S., Shariza; Z.M., Rosli; Azizah, Shaaban; Sivarao, Subramonian; Mohamad, Radzai Said; S., Thiru (IDOSI Publications, 2013)
The objectives of this paper is to synthesise the ternary molybdenum sulphoselenide MoSSe thin films via electrodeposition technique and analyse the effect of film thickness to its optical and semiconducting properties. Transition metal molybdenum sulphoselenide, MoSSe thin films have been electrosynthesized on indium-tin-oxide (ITO)-coated glass and stainless steel substrates. The thin films were characterized for their structural, surface morphological, compositional characteristics as well as optical properties and semiconducting parameters. Structural analysis via X-ray diffraction (XRD) reveals that the films are polycrystalline in nature. Scanning electron microscope (SEM) studies reveal the morphology of the film with crystallites on the surface. Compositional analysis via energy dispersive X-ray (EDX) analysis confirms the presence of Mo, S and Se elements in the films. The optical studies show that the films are of direct bandgap. Results on the semiconductor parameters analysis of the films showed that the nature of the Mott-Schottky plots indicates that the films obtained are of n-type material. For all films, the semiconductor parameter values come in the potential range of leading chalcogenides as a semiconductor thin film which can be suitable for photo electrochemical solar cell in the near future.